Center-Based Care for Infants and Toddlers: The aeioTU Randomized Trial (2018)
Extensive research has shown comprehensive early intervention can improve the developmental outcomes of disadvantaged children. However, little is known about the effectiveness of center-based programs for infants and toddlers; relatively rare in the developing world and typically of low quality. This paper reports effects from a randomized trial of a center-based early care intervention on infants and toddlers in two communities in northern Colombia. Just eight months into the program results indicate large positive effects on language, cognitive development and overall development, with girls benefitting the most. No effects were observed for nutritional outcomes, socio-emotional development or the home environment.